Faecal Streptococci in Fresh Frozen Shrimp - Iyer, T. S. Gopalakrishna; Mathew, Annamma; Joseph, A. C.; Rao, K. Krishna; Pillai, V. K. (Fishery Technology, 1973)
Present limit of Faecal streptococci as 100 /g in fresh frozen shrimp was found to be too strict  a standard for commercially prepared products. Statistical analysis of the data collected indicates that fixing the maximum permissible limit as 1000/g will be a more workable proposition.